Normal values and regional differences in oesophageal impedance-pH metrics: a consensus analysis of impedance-pH studies from around the world. Issue 8 (9th October 2020) - Sifrim, Daniel; Roman, Sabine; Savarino, Edoardo; Bor, Serhat; Bredenoord, Albert J; Castell, Donald; Cicala, Michele; de Bortoli, Nicola; Frazzoni, Marzio; Gonlachanvit, Sutep; Iwakiri, Katsuhiko; Kawamura, Osamu; et al.
Abstract : Objective: Limitations of existing impedance-pH thresholds include small sample size of normative studies, inclusion of artefactual pH drops and incorrect identification of impedance reflux events. We aimed to obtain new impedance-pH thresholds from expert consensus analysis of tracings from a large number of healthy subjects. Design: Of 541 studies performed worldwide using two different systems (Diversatek, USA, and Laborie, Netherlands), 150 tracings with oesophageal diagnoses, behavioural disorders and study-related artefacts were excluded. The remainder studies were subject to two reviewer consensus analysis, in-person or through video conference, consisting of editing meals and pH drops, identification of impedance reflux and postreflux swallow-induced peristaltic wave (PSPW) using strict pre-established criteria and measurement of distal mean nocturnal baseline impedance (MNBI). Results: Consensus analysis was performed in 391 tracings (age 32.7 years, range 18–71, 54.2% female). Normative thresholds were significantly different between Diversatek and Laborie (total acid exposure time: 2.8% and 5%; reflux episodes: 55 and 78; MNBI at 3 cm: 1400 and 1500 ohms, at 5 cm: 1400 and 1800 ohms). Males had higher acid exposure, more reflux episodes and lower MNBI. Significant regional differences were identified, including higher PSPW scores in Western countries, and higher MNBI in Asia using Diversatek, and higher acid exposure in the Netherlands, higher MNBI in Asia and South Africa, and lower MNBI in Turkey using Laborie. Conclusion: Normal impedance-pH monitoring thresholds have regional and system-related differences. Clinical interpretation needs to use normal thresholds valid for the system used and world region, following careful editing of the tracings.